2011
DOI: 10.5012/bkcs.2011.32.2.553
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antibacterial Applications of Novel Copolymeric Silver Nanocomposite Hydrogels

Abstract: Copolymeric silver nanocomposite hydrogels were synthesized by using acryloyl phenylalanine (APA), N'-isopropylacrylamide (NIPAM) and crosslinked by N,N-methylene bisacrylamide (MBA) via radical redox polymerization. Present study allows entrapping silver nanoparticles into hydrogel networks. UV-visible spectroscopy and X-ray diffraction (XRD) studies confirmed the formation of silver nanoparticles in hydrogel matrix. 11% of weight loss difference between hydrogel and silver nanocomposite hydrogel is clearly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…21,22 Moreover, polymeric nanoparticles reduce concerns regarding the cytotoxicity of AgNPs because the gel limits the direct exposure of a patient's cells to AgNPs and release AgNPs slowly. 23,24 Previously, it was reported that encapsulation of AgNPs inside a polymeric nanoparticle did not affect the size and morphology of the nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Moreover, polymeric nanoparticles reduce concerns regarding the cytotoxicity of AgNPs because the gel limits the direct exposure of a patient's cells to AgNPs and release AgNPs slowly. 23,24 Previously, it was reported that encapsulation of AgNPs inside a polymeric nanoparticle did not affect the size and morphology of the nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
“…25 Polymeric nanoparticles are an attractive vehicle for sustained AgNP release during local therapy because of their tunable size, numerous functional groups, thermo-responsiveness, high loading capacity, good stability, biocompatibility, and anionic charge. 21,24,26 In this study, we fabricated three sizes of two polymeric nanoparticle types: poly-N-isopropylacrylamide (pNIPAM) and pNIPAM-NH 2 . In each polymeric nanoparticle, we encapsulated three different concentrations of AgNPs using a water-soluble reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…More Ag nanoparticles are formed mainly around the PAPSQ particles. Several studies have reported silver nanocomposite membranes and hydrogels . According to the literature, silver nanoparticles are formed inside networks due to the anchoring capacity of the network chains.…”
Section: Resultsmentioning
confidence: 99%
“…fine chemicals, Mumbai, India. Acryloyl phenylalanine (APA) was synthesized as reported in earlier studies [16].…”
Section: Methodsmentioning
confidence: 99%